Standalone immersion cooling of computing server - Tan, Gareth Yu Shu (2019)
The motivation of this study is to investigate the effectiveness and efficiency of immersing a computer server into a tank filled with a dielectric liquid, the Novec 7100 engineered fluid, in order to cool its large power distribution components. This process is known as two phase immersion cooling of a computer server. This method of cooling computer servers has been gaining popularity across the world, especially for data centers that are focusing on greener methods to cool their servers. This is because it allows the operator to reduce their energy usage drastically, since it eliminates the need of an expensive air cooling infrastructure which includes on board server fans, computer room air conditioning, air conditioning compressors, airIcirculation fans, necessaryIduct work and air handlers. Thus, this project aims to study the effectiveness of cooling a computer server by two phase liquid immersion cooling. This report presents the results of an investigation into the effectiveness of two phase immersion cooling of a computer server. This is done by immersing a computer server into a specially designed tank filled with a dielectric liquid, which is the Novec 7100 engineered fluid. Tests involving having the computer is running at 0 percent, 50 percent and 100% stress load and recording the temperature of the computer server while it is operating in different environments were ran. These environments include, an air conditioned room and by immersing the computer server in Novec 7100 engineered fluid. The differences in the temperatures were recorded, and the experiment findings found that by the temperature recorded by immersing the computer server in the Novec 7100 engineered fluid is lower and the rate of cooling is faster. Future work that can be done from this project include trying different possible dielectric liquid coolant and investigating the effectiveness of each, emulating a data centre and having multiple computer servers immersed in a bigger tank, and having the computer server in immersion cooling for an extended period of time.